DESIGN AND DEVELOPMENT OF ORAL SUSTAINED RELEASE MATRIX TABLETS OF DIDANOSINE - SOUMYA, P.; RAO, N. G. RAGHAVENDRA; KISTAYYA, C.; REDDY, B. MAHIPAL (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: In present study, an attempt was made to design sustained-release tablets containing Didanosine using natural gums like Xanthan gum, Guar gum and Karaya gum. Methods: The sustained-release tablets containing Didanosine prepared by using natural gums by wet granulation method. Influence of natural polymer on Didanosine was studied. The prepared tablets were selected for DSC and FTIR studies. Results and Discussions: The tablets were selected for DSC and FTIR studies did not show any chemical interaction between drug and polymer. The prepared formulations were evaluated for Hardness, Thickness, Friability, Weight variation, drug content estimation, Swelling index, in-vitro drug release are within the acceptable standard. In-vitro release profile was check for 8 hrs to evaluate the SR matrix tablet of Didanosine. The optimized tablets were carried out according to ICH guidelines at 40 ± 2º C/ 75 ± 5percent RH for three months. All the prepared tablets were stable at room temperature. The values of pre-compression parameters of prepared granules were evaluated the results were within prescribed limits and indicated good free flowing property. The prepared tablets were subjected to all the quality control tests they were within the official pharmacopoeial limits. Friability is less than 1percent, indicated that tablets had a good mechanical resistance. Weight variation test revealed that the tablets were within the range of pharmacopoeial limit. Thickness, hardness and drug content were within the range of pharmacopoeial limit. The evaluation parameters were within acceptable range for all the formulations. The in-vitro release of Didanosine was conducted for 8 hrs. The optimized formulations WGX3, WGG5 and WGK9 sustained the release up to 8hr. Hence Didanosine along with Xanthan gum, Guar gum and Karaya Gum could be used to prepared sustained released matrix tablets. The in-vitro release obeyed zero order kinetics with mechanism of release was erosion followed by non-fickian diffusion. Conclusion: Among all the formulations WGK9 is the best shows excellent release around 99percent after 8 hrs. The prepared matrix tablets of Didanosine were stable. So, it may be concluded that sustained release matrix tablets would improve the patient compliance and bioavailability may be improved. Keywords: Didanosine, Xanthan gum, Guar gum and Karaya gum.